Predicting the distribution of Sphagna (Bryophyta) in Türkiye: a perspective of present and future climate scenarios - Abay, Gökhan; Gül, Serkan (Frontiers in Plant Science, 2025)
Climate change is a fact that impacts all living organisms. To understand its effects, numerous methods and techniques have been refined in recent years, with species distribution modeling (SDM) being one of the most widely used. This study applied SDM to examine the distribution of seventeen Sphagnum species, a group of non-vascular land plants throughout Türkiye, under changing climate conditions. The study considered one global climate model (GCM)—BCC-CSM2-HR—two scenarios (SSP1-2.6 and SSP5-8.5), and two time periods (2021–2040 and 2081–2100). For the SDM analysis, a total of 211 occurrence records for whole species were used. According to the results, the future status of some species is similar to the current status, but some species show differences. Especially in the SSP5-8.5 scenario of the 2081-2100 time period, it is seen that there is a decrease in the distribution patterns of the integrals. Our study shows a simulation of the future distribution of these Sphagnum mosses, which have the ability to hold a lot of water, thus providing valuable information for the conservation of these species at both local and regional levels across Türkiye.